Stroke: clinical characterization and outcomes post hospital discharge: (Research, Society and Development, 2020)
Objective: To associate the clinical profile of people with stroke to post hospital discharge outcomes. Method: documentary study carried out in a reference unit for stroke in the interior of Brazil’s northeast. The sample consisted of 279 medical records from which data were collected regarding the clynical variables for association with the post discharge outcome. The data were analyzed using bivariate statistics, with the application of statistical tests considering the significance of p